2008
DOI: 10.1103/physrevlett.100.099901
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Spatiotemporal Stability of a Femtosecond Hard–X-Ray Undulator Source Studied by Control of Coherent Optical Phonons [Phys. Rev. Lett.99, 174801 (2007)]

Abstract: In our recent Letter, the atomic displacement given on the right axis of Fig. 5 was mistakenly overestimated by a factor of 4.2. The conclusions made in the Letter are not affected by our error.FIG. 5 (color online). Measured (symbols) and simulated (solid curves) bismuth (111) coherent optical phonon oscillation controlled by a 2-pulse excitation scheme. The absorbed energy density per pulse was 1:12 mJ=cm 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
83
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 0 publications
2
83
0
Order By: Relevance
“…Recently there has been considerable interest in the dynamics of the A 1g mode in the limit of a dense electronhole plasma, particularly for bismuth [21][22][23][24][25][26][27][28][29] . Hase et al 24 observed that the frequency of the mode is impulsively softened and chirped toward the equilibrium value over a few picoseconds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been considerable interest in the dynamics of the A 1g mode in the limit of a dense electronhole plasma, particularly for bismuth [21][22][23][24][25][26][27][28][29] . Hase et al 24 observed that the frequency of the mode is impulsively softened and chirped toward the equilibrium value over a few picoseconds.…”
Section: Introductionmentioning
confidence: 99%
“…Both humps are separated by a dip from which the modulated electrons have been removed. X-ray diffraction measurements on the phonon dynamics of photo-excited bismuth are consistent with an effective x-ray pulse duration and, thus, the full width at half maximum (FWHM) of the humps is ð140 AE 30Þ fs [9].…”
Section: Fundamentalsmentioning
confidence: 68%
“…[9,10]. Briefly, the slicing laser is a regenerative Ti:Sa amplifier with a pulse duration of 70 fs FWHM, a repetition rate of 2 kHz, and a maximum pulse energy of 2.5 mJ.…”
Section: Fundamentalsmentioning
confidence: 99%
“…Therefore, one can investigate the lattice dynamics that result from high-amplitude phonon motions independent of the electronic or thermal contributions. * yuhsiang@mit.edu † Corresponding author: kanelson@mit.edu Although the excitation of bismuth with a pair of optical pump pulses has been probed experimentally several times in the literature [4,[7][8][9][10][11][12][13], almost none have fine interpump delay steps and a long delay window in the interpump delay due to the time-intensive nature of performing a two-dimensional (2D) pump-probe measurement. With single-shot spectroscopy, we can acquire a pump-probe trace with one laser shot and thus reduce the dimension of the delay scan down to 1.…”
Section: Introductionmentioning
confidence: 99%